2017
DOI: 10.1590/1807-01912017233714
|View full text |Cite
|
Sign up to set email alerts
|

A eficácia do pork barrel: a importância de emendas orçamentárias e prefeitos aliados na eleição de deputados

Abstract: IntroduçãoPesquisas de opinião junto a eleitores e deputados sugerem que garantir repasses financeiros para os redutos eleitorais é um imperativo da sobrevivência política no Brasil (Ames, Baker e Rennó, 2008; Lemos e Ricci, 2011). A mídia e a academia, por sua vez, frequentemente desenvolvem suas análises assumindo que essa premissa seja verdadeira.Acontecimentos recentes, como a aprovação da Emenda Constitucional 86/2015, reforçam essa visão, uma vez que deputados e senadores se uniram para aprovar, por maio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
1
0
5
Order By: Relevance
“…However, studies indicate that Congress funding tends to be directed towards municipalities where there is political party affinity between the mayor and the Federal Government, 18 and between the mayor and the parliamentarian allocating Congress funding. 19 The following finding stands out with regard to HFCP adherence distribution, from the perspective of municipal socioeconomic development, in general, municipalities with higher adherence indicators fall into the group with moderate to high Firjan Socioeconomic Development Indicators, while municipalities with low to regular Firjan Socioeconomic Development Indicators showed a negative relationship between adherence indicators and NCD indicators. These findings differ from those of another recent study, which demonstrated that almost half the municipalities taking part in the HFCP fell into the category of the lowest Municipal Human Development Index (IDHM).…”
Section: Discussionmentioning
confidence: 87%
“…However, studies indicate that Congress funding tends to be directed towards municipalities where there is political party affinity between the mayor and the Federal Government, 18 and between the mayor and the parliamentarian allocating Congress funding. 19 The following finding stands out with regard to HFCP adherence distribution, from the perspective of municipal socioeconomic development, in general, municipalities with higher adherence indicators fall into the group with moderate to high Firjan Socioeconomic Development Indicators, while municipalities with low to regular Firjan Socioeconomic Development Indicators showed a negative relationship between adherence indicators and NCD indicators. These findings differ from those of another recent study, which demonstrated that almost half the municipalities taking part in the HFCP fell into the category of the lowest Municipal Human Development Index (IDHM).…”
Section: Discussionmentioning
confidence: 87%
“…A popularidade do governo é marca da legitimação social e os vereadores tendem a agir buscando legitimar-se frente ao Prefeito, fazendo parte da coalizão. Quando o vereador faz parte da coalizão e consegue ter executado algum projeto que apresenta, ele cria junto ao seu eleitorado a reputação de competente, facilitando a sua reeleição (Baião & Couto, 2017, Raupp & Pinho, 2012, Desposato, 2008. Ao contrário, se o vereador não está na coalizão, busca a legitimação frente ao eleitorado, negociando individualmente seus projetos com o Executivo, valendo-se da própria reputação.…”
Section: Teoria Institucional Sociológica De Legitimação E a Formação...unclassified
“…A literatura categoriza tais instrumentos como pork barrel spending, expressão em inglês que designa políticas distributivas cujos benefícios (e beneficiários) do gasto concentram-se em uma localidade ou reduto eleitoral específico, enquanto os custos delas derivados são dispersos, via tributação, para uma base geográfica mais ampla (LANCASTER, 1986;LAZARUS, 2010;BAIÃO;COUTO, 2017).…”
Section: Emendas Parlamentares: Distorções E Sistema De Incentivosunclassified